2019
DOI: 10.1111/rsp3.12200
|View full text |Cite
|
Sign up to set email alerts
|

Cultural tourism and rural entrepreneurship: A case study of a Scandinavian literary festival

Abstract: Tourism demand within peripheral regions reflects visitor motivations to seek experiences constrained by attributes that involve the abilities of these visitors. Often, the basis of tourism supply is driven by accessible publicly-owned common-pool resources that exist as regional economic assets yet are unpriced in the marketplace. Free-riding prevails as rent-seeking firms utilize non-marketed natural and cultural assets in their production practices. The work reported here develops concepts that illustrate k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Studies have noted that policy support for RHT development is now part of several countries' hospitality and tourism development strategies because of its positive economic impact on the local community (Kubickova and Campbell, 2020;Richard Sharpley, 2002;Situmorang et al, 2019). Furthermore, the public-private partnership has also been a significant avenue of value creation for the RHT enterprises and community (Marcouiller and Westeren, 2019). Prior studies have observed that governments have made and continue to make an active effort in supporting RHT enterprises by providing support and resources such as training (Hern andez-Maestro et al, 2009; Wang and Man, 2019), finance, consulting (Situmorang et al, 2019) and marketing (Kubickova and Campbell, 2020).…”
Section: Institution-level Enablersmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have noted that policy support for RHT development is now part of several countries' hospitality and tourism development strategies because of its positive economic impact on the local community (Kubickova and Campbell, 2020;Richard Sharpley, 2002;Situmorang et al, 2019). Furthermore, the public-private partnership has also been a significant avenue of value creation for the RHT enterprises and community (Marcouiller and Westeren, 2019). Prior studies have observed that governments have made and continue to make an active effort in supporting RHT enterprises by providing support and resources such as training (Hern andez-Maestro et al, 2009; Wang and Man, 2019), finance, consulting (Situmorang et al, 2019) and marketing (Kubickova and Campbell, 2020).…”
Section: Institution-level Enablersmentioning
confidence: 99%
“…4.1.2 Demand-side barriers. The tourist side, that is, the demand side of the hospitality and tourism equation has a significant impact on how RHT enterprises function (Ikonen, 2016;Marcouiller and Westeren, 2019). The chief objective of RHT is the commodification of tourist destinations, used here to refer to the packaging of rural experiences for tourist consumption.…”
Section: Institution-level Enablersmentioning
confidence: 99%
“…Shows, like other festivals, can strengthen and integrate place identity and a sense of community (Jarman, 2018; Hjalager and Kwiatkowski, 2018). The Show experience is representative of the local heritage and natural amenities that comprise a contemporary multi-functional rural landscape (Marcouiller and Westeren, 2019). By expanding their identity and reflecting increasing business diversity in the rural economy (DEFRA, 2019), Shows now provide networking and promotional opportunities beyond the agriculture and food sectors.…”
Section: Agriculture Shows and Their Role In The Rural Economymentioning
confidence: 99%
“…Among museums and heritage attractions, more interactive forms of information and communication technology (ICT) have been used to augment understanding and accessibly for tourists (Hjalager, 2010) but even this remains a largely static addition to the physical experience. However, combining wholly online events with physical ones and developing interactivity between the two spaces, allows organisers to conceive new experiencescapes (Marcouiller and Westeren, 2019) or eventscapes (Brown et al , 2015) to improve the visitor offering both online and at the Showground. Both the e-servicescape and eventscape models are therefore valuable for evaluating the innovation of online Shows.…”
Section: Rural Events Innovationmentioning
confidence: 99%
“…Currently, the main goals of public-private partnership in the tourism industry are to attract investment in the development of business, sports, cultural and educational types of tourism. Research results show that public-private partnership projects can be used to stimulate entrepreneurship (Marcouiller and Westeren, 2019). The involvement of the private sector in the management of tourist infrastructure facilities can help to increase their economic efficiency, achieve high performance in the organization of public recreation, security, and financial return (Ly and Zhang, 2019).…”
Section: Introductionmentioning
confidence: 99%